2008
DOI: 10.1370/afm.776
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Uncontrolled Asthma in Family Practice Using a Mailed Asthma Control Questionnaire

Abstract: PURPOSE A substantial proportion of adult patients with asthma have inadequately controlled symptoms despite the availability of effective treatment. The Asthma Control Questionnaire (ACQ) can be used to discriminate between asthma patients with well-and suboptimally controlled asthma symptoms. The objective of this study was to investigate whether a postal mailing of the ACQ can be used to identify asthma patients with suboptimal symptom control in family practice. METHODSIn this observational study, we sent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In this study, the frequency and severity of symptoms were sufficient that three quarters (76%) could be classified as uncontrolled. Given that uncontrolled asthma is reported at approximately 60% in general practice populations [20,21], the high rate of uncontrolled symptoms among children with moderate to severe asthma in this study is not completely unexpected and highlights the under-management of asthma in the pediatric population [11]. Although studies such as this one indicate that symptom control is achieved far less optimally in real world practice settings, it has been shown that asthma control can be achieved and maintained in the majority of patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the frequency and severity of symptoms were sufficient that three quarters (76%) could be classified as uncontrolled. Given that uncontrolled asthma is reported at approximately 60% in general practice populations [20,21], the high rate of uncontrolled symptoms among children with moderate to severe asthma in this study is not completely unexpected and highlights the under-management of asthma in the pediatric population [11]. Although studies such as this one indicate that symptom control is achieved far less optimally in real world practice settings, it has been shown that asthma control can be achieved and maintained in the majority of patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…patients should not experience any symptoms. However, in daily practice, a considerable proportion of asthma patients continuously experience symptoms without consulting their physician [ 49 ]. This raises the question of patient's preferences with regard to treatment aims.…”
Section: Discussionmentioning
confidence: 99%
“…In these circumstances, most guidelines recommend the next treatment step [37]. However, this situation may persist for a longer period as patients do not always seek medical attention [38]. An arbitrary line to differentiate between situations A and B on the Y-axis could be an Asthma Control Questionnaire score of 0.75 ACQ 150 [39,40 ].…”
Section: Towards a Prospective Definitionmentioning
confidence: 99%